2007
DOI: 10.4219/jaa-2007-703
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Academic Motivation in Culturally and Linguistically Diverse Students From Low Socioeconomic Backgrounds

Abstract: According to research, students from culturally and linguistically diverse backgrounds have lower rates of high school graduation and university attendance. There is little research regarding interventions to address these issues. The current study compared the effects of two programs designed to increase academic motivation. Forty-seven high school female athletes from culturally and linguistically diverse and economically disadvantaged backgrounds participated in the study. The programs were implemented over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Other researchers have found connections between a student's sense of belonging to a school, their engagement and development of important cognitive skills, and ultimately their achievement (Bryk & Schneider, 2002;Klem & Connell, 2004;Osterman, 2000;Walker & Greene, 2009). Evaluation literature of particular school SEL programs and case studies of schools also support these findings, including a number of case studies of urban public schools (Alexander-Snow, 2011;Cholewa, Amatea, West-Olantunji, & Wright, 2012;Del Prete, 2010;Kaylor & Flores, 2007;Lieber, 2009;Quint, 2006;Rhodes, Stevens, & Hemmings, 2011;Thompson & Ongaga, 2011).…”
Section: Prior Literaturementioning
confidence: 89%
“…Other researchers have found connections between a student's sense of belonging to a school, their engagement and development of important cognitive skills, and ultimately their achievement (Bryk & Schneider, 2002;Klem & Connell, 2004;Osterman, 2000;Walker & Greene, 2009). Evaluation literature of particular school SEL programs and case studies of schools also support these findings, including a number of case studies of urban public schools (Alexander-Snow, 2011;Cholewa, Amatea, West-Olantunji, & Wright, 2012;Del Prete, 2010;Kaylor & Flores, 2007;Lieber, 2009;Quint, 2006;Rhodes, Stevens, & Hemmings, 2011;Thompson & Ongaga, 2011).…”
Section: Prior Literaturementioning
confidence: 89%
“…The same is the case for programs meant to bolster only positive possible identities. These programs typically emphasize positive possible identities and ignore negative ones or treat them as to-be-abandoned (Kaylor & Flores, 2007). Since contexts are unlikely to be uniformly success-likely, these approaches are unlikely to yield robust effects over time.…”
Section: Implications For Research and Interventionmentioning
confidence: 97%
“…They report that their "findings are consistent with results obtained among college students" (Curry et al, 1997) and older adults (Chang, 2003), suggesting that academic and intrapersonal variables are differentially related to hope levels among school-age youth" (p. 175). Kaylor and Flores (2007) identify culturally and linguistically diverse students in the United States as being a particularly vulnerable group o f students, with lower high school graduation rates and university attendance. They identified that previous researchers "found that certain factors are common among high-achieving minority students" (p. 68).…”
Section: Hope Theory In Educational Settingsmentioning
confidence: 99%
“…One o f those factors, identified by several of the studies, was goal orientation. Kaylor and Flores (2007) designed a study o f two groups o f students, one group participated in a program designed by the athletic department and the other group participated in a program called Possible Selves. "The concept of possible selves contains the premise that an individual sets goals and then creates a plan for meeting those goals by discerning aspirations and envisioning what and who they want to become" (p. 70).…”
Section: Hope Theory In Educational Settingsmentioning
confidence: 99%
See 1 more Smart Citation